2017
DOI: 10.1007/s12029-017-9985-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Correlation of EZH2 and Cancer Stem Cell Markers in Esophageal Squamous Cell Carcinoma

Abstract: To the best our knowledge, there are variety of small molecule inhibitors to target EZH2 in cancer cells as a treatment candidate; therefore, our data in this study helps the researchers to select EZH2 for cancer therapy based on its mechanism and correlation with other markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…28 In the current study, EZH2 was significantly upregulated in ESCC cells and tumor tissues, which was consistent with previous research. 29 Knockdown of EZH2 had the same effect on apoptosis and protein expression as overexpression of miR-101-3p. Thus, we hypothesized that miR-101-3 affects apoptosis in ESCC cells by regulating EZH2 expression.…”
Section: Dovepressmentioning
confidence: 93%
“…28 In the current study, EZH2 was significantly upregulated in ESCC cells and tumor tissues, which was consistent with previous research. 29 Knockdown of EZH2 had the same effect on apoptosis and protein expression as overexpression of miR-101-3p. Thus, we hypothesized that miR-101-3 affects apoptosis in ESCC cells by regulating EZH2 expression.…”
Section: Dovepressmentioning
confidence: 93%
“…Previous research has demonstrated that EZH2 plays critical roles in the epigenetic silencing of target genes and modulates the proliferation and metastasis of cancer cells (Huqun et al, ; Varambally et al, ). The upregulation of EZH2 has been discovered in many cancer cells, such as non‐small‐cell lung cancer (Huqun et al, ), breast cancer (Chase & Cross, ), esophageal squamous cell carcinoma (Karami Madani et al, ), and colon cancer (Ferraro, Boni, & Pintzas, ). For colon cancer, Ferraro et al (Ferraro et al, ) reported that EZH2 regulated cofilin activity and colon cancer cell migration via targeting integrin α 2 (ITGα 2).…”
Section: Introductionmentioning
confidence: 99%
“…revealed that MAGI2-AS3 can down-regulate HOXB7 expression by recruiting EZH2 to initiate the upregulation of H3K27me3 protein expression. As a stemness factor, EZH2 possesses the ability to regulate cell differentiation, embryonic development and cancer development, such that EZH2 silencing demonstrably down-regulates various genes in ESCC (Karami Madani et al, 2018). The indispensable role of H3K27me3 in EZH2-mediated repression of genes in tumorigenesis and tumor progression has also been documented, while expression of H3K27me3 and EZH2 are indicative of poor prognosis of patients with ESCC (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a stemness factor, histone methyltransferase EZH2 has the ability to regulate cell differentiation, embryonic development, and cancer development, and EZH2 silencing has been confirmed to downregulate different genes in ESCC (Karami Madani et al, 2018). H3K27me3 is required for EZH2-mediated repression of various genes essential for tumorigenesis and tumor development, while the expression of H3K27me3 and EZH2 could serve as biomarkers in the prediction of ESCC patients' survival and ESCC metastasis (Liu et al, 2016).…”
Section: Magi2-as3 Down-regulates Hoxb7 By Recruiting Ezh2 To Initiatmentioning
confidence: 99%